The Effect of Little Alchemy 2 Game Duration on Figural Creativity in Adolescence - Fakhri, Nurfitriany; Budi, Muhammad Anugerah; Tetteng, Basti; Buchori, Sahril (Indonesian Journal of Educational Studies, 2023)
There are multiple methods to cultivate creativity, including play. In current times, teenagers frequently engage in smartphone-based play, leading to the emergence of online gaming as a solution. Little Alchemy 2 is a popular game among teenagers. This study aims to determine the effectiveness of the duration of little alchemy 2 game play on adolescent figural creativity in Makassar city. This study used a one group pre-test post-test experimental design by comparing experimental group 1 with a time limit of 1 minute and experimental group 2 with a time limit of 30 minutes. The study involved 30 male students aged 18-19. The statistical tests employed in this study were the Mann Whitney Test and the Wilcoxon Test. The results of this study indicate that there is an effect of intensity in playing the game little alchemy 2 with ρ = 0.042 (ρ <0.05), and there is a difference between the intensity of experimental group 1 and experimental group 2 in playing games at p = 0.000 small than (<0.005). Engaging in Little Alchemy 2 gameplay for a duration of 15 to 30 minutes has the potential to augment the creativity of adolescents.